Study of acute febrile illness with thrombocytopenia in a tertiary care centre - Fawas N., Mohammed; Beevi B., Kadeeja; Valliyot, Balakrishnan; Balakrishnan, Sudha (International Journal of Research in Medical Sciences, 2018)
Background: In the recent period there is an upsurge in the incidence of fever with thrombocytopenia in the Northern Kerala. This may be due to the several emerging and re emerging infections which causes frequent epidemics in the region. Early diagnosis and meticulous management will prevent fatal out come. Studies on fever with thrombocytopenia are very few in the Northern part of Kerala. Methods: This was a descriptive study conducted at Academy of Medical Sciences Pariyaram over a period of one year from November 2015 to October 2016. The study includes 251 cases attending outpatient and inpatients units in the department of medicine. All patients with a platelet count less than 150000 was included in this study and detailed clinical and laboratory evaluation was done and assessed for the etiology and outcome. Results: Among the 251 cases, Dengue fever accounts 54.5 % of cases and 26.2% are other viral fever where the exact causative organism was not detected. Leptospirosis, malaria were also important causes of fever with thrombocytopenia. Major incidence of hemorrhagic manifestation occurred in the age group of 20 to 30 years whose platelet count was in the range of 10000 to 40000/mm3. Conclusions: In this study more than 50 % had dengue fever and in 26.2% cases an exact etiology cannot be determined. This finding highlights the fact that there may be many unidentified infection which cause fulminant thrombocytopenia and there is a need for wider screening of infection.